Evaluation of Reorientation Techniques and Distractors for Walking in Large Virtual Environments - Peck, T.C.; Fuchs, H.; Whitton, M.C. (IEEE transactions on visualization and computer graphics, 2009)
Virtual environments (VEs) that use a real-walking locomotion interface have typically been restricted in size to the area of the tracked lab space. Techniques proposed to lift this size constraint, enabling real walking in VEs that are larger than the tracked lab space, all require reorientation techniques (ROTs) in the worst-case situation-when a user is close to walking out of the tracked space. We propose a new ROT using visual and audial distractors-objects in the VE that the user focuses on while the VE rotates-and compare our method to current ROTs through three user studies. ROTs using distractors were preferred and ranked more natural by users. Our findings also suggest that improving visual realism and adding sound increased a user's feeling of presence. Users were also less aware of the rotating VE when ROTs with distractors were used.